Microwave Absorption Potential of La0.7[X0.95Y0.05]0.3MnO3 with Dual-Doped Sites XY = (Ca,Ba), (Ca,Sr), and (Sr,Ba) - Apriatin, Apriatin; Saptari, Sitti Ahmiatri; Tjahjono, Arif (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
The technology in the field of electronic devices is currently advancing in line with the increasing usage by humans. This continuous and growing usage also increases the amount of microwave radiation generated. This leads to wave interference that can disrupt the functionality of application devices. Absorbing materials are a type of material that functions as a microwave absorber. This study engineered lanthanum manganate material, specifically La0.7[X0.95 Y0.05]0.3MnO3 XY = (Ca,Ba), (Ca,Sr), and (Sr,Ba), synthesized using the sol-gel method. The X-Ray Diffraction characterization results showed that each sample has a single-phase orthorhombic structure with a space group of Pbnm (62). The Scanning Electron Microscope–Energy Dispersive Spectroscopy characterization revealed particle morphology with varying particle size distributions on a micro-scale. Based on Vibrating Sample Magnetometer results, the samples La0.7[Ca0.95Ba0.05]0.3MnO3 and La0.7[Ca0.95Sr0.05]0.3MnO3 exhibit paramagnetic properties, while La0.7[Sr0.95Ba0.05]0.3MnO3 exhibits superparamagnetic properties. Through Vector Network Analyzer characterization, it was found that lanthanum manganate doped with Ca, Ba, and Sr demonstrated high electromagnetic wave absorption capabilities, achieving an absorption rate of 97%–98% at frequencies of 10–10.5 GHz. Thus, La0.7[X0.95 Y0.05]0.3MnO3 XY = (Ca,Ba), (Ca,Sr), and (Sr,Ba) is a potential candidate as a microwave-absorbing material.